A Syntactic Analysis Of Noun Phrase In The Texts Of Developing English Competencies Book For X Grade Of Senior High School - Sari, Diana Kusuma (2012)
This research deals with Noun Phrase in the genre text of Developing English Competencies book by Achmad Doddy. The aims of this research are to identify the constituent of the Noun Phrase and to describe the structural ambiguities of the Noun Phrase in the genre text. The type of this research is descriptive qualitative. The data source of this research is the genre text book by Achmad Doddy, Developing English Competencies Book. The researcher takes 145 data of noun phrase in sentences of Developing English Competencies Book. The method of collecting data is documentation and the steps are reading, indentifying, collecting and coding the data. The method of analyzing data is comparative method. The analysis of the data is by reffering to the context of syntax by using tree diagram in the theory of phrase structure rules then presenting phrase structure rules and phrase markers. This study shows the constituents of noun phrase in sentences used in genre text book. The constituents of noun phrase are (1) A, (2) D, (3) APP, (4) DPa, (5) DPc, and (6) PN.